Postęp i możliwości zastosowania genomiki w hodowli drzew leśnych - Szyp-Borowska, Iwona (Leśne Prace Badawcze, 2010)
A variety of new molecular techniques and dynamic development of bioinformatics have enabled the research on organization and functioning of forest tree genomes. According to estimates, the number of genes of forest trees totals about 30 thousand. Identification of these genes and determination of their locations on genetic maps is the major task of structural genomics. The application of genome analysis method and determination of molecular markers linked to a region of chromosomes, containing a gene affecting the target trait, can be used in applied tree breeding programs.